2011
DOI: 10.1016/j.jpainsymman.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Education in China: Insight Into One Medical University

Abstract: Palliative care education is inadequate from the perspective of the Chinese medical interns. An improvement in the medical school curriculum is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…Although palliative care is now widely available in Western countries, it is extremely limited in mainland China . According to a 2016 report, only 0.7% (146/22,000) of hospitals offered palliative care .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although palliative care is now widely available in Western countries, it is extremely limited in mainland China . According to a 2016 report, only 0.7% (146/22,000) of hospitals offered palliative care .…”
Section: Introductionmentioning
confidence: 99%
“…Although palliative care is now widely available in Western countries, it is extremely limited in mainland China [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo realizado por Jiang et al 18 na China com o intuito de avaliar o conhecimento dos estudantes de Medicina chineses sobre conceitos de cuidados paliativos corrobora os resultados encontrados no presente estudo: 58,9% dos acadêmicos responderam estar preparados para lidar com cuidados terminais do paciente, enquanto apenas 7,5% se consideraram adequadamente preparados para lidar com a gestão da dor, e 13% adequadamente treinados para controlar os sintomas de pacientes em estado terminal.…”
Section: Discussionunclassified
“…Secondly, the lack of professionally trained health-care providers and administrators is another major barrier. A survey among interns in a Chinese Medical University (N=400) [13] showed that less than 10% of the them felt competent in basic pain management, and nearly 80% did not feel adequately trained in discussing death with patients and family members. Thirdly, there are several administrative and policy problems.…”
Section: National Hospice Service Program (Nhsp) Funded By LI Ka Shinmentioning
confidence: 99%
“…Thirdly, there are several administrative and policy problems. For example, most hospitals in China must generate their own incomes, and since palliative care is not very profitable, it is usually overlooked by the hospitals and clinicians [13]. Fourthly, a shortage of funding and donations to support the development of palliative care is also a barrier in mainland China.…”
Section: National Hospice Service Program (Nhsp) Funded By LI Ka Shinmentioning
confidence: 99%